Manipulation Under the Mask of Justice - Keleş, Aybike (Akademik Sosyal Arastirmalar Dergisi (Asya Studies), 2024)
Bertolt Brecht’s Round Heads and Pointed Heads, initially performed in Denmark in 1936, criticizes an unjust legal system where marginalized individuals are silenced and their grievances remain unheard, while those in the position of power are given preferential treatment. At the beginning of the play, the monarch of Luma relinquishes sovereignity of the nation to the Iberin authority as a means to quell civil unrest stemming from the economic turmoil. Consequently, a new law is enacted promoting the principles of equality, and justice is promoted for the first time in society. The Iberian government manipulates public perception by disseminating a conspiracy theory that serves its political agenda. Blind obedience in society is perpetuated through the stereotypes that associate the pointed heads with deceit and immorality while portraying the rounded heads as examples of honesty and loyalty. To demonstrate equal treatment under the law, Iberin imposes a penalty on a landlord with a pointed head for the sexual abuse of a working-class young girl with a round head. At the conclusion of the play, the landlord’s acquittal as a result of his privileged social standing raises concerns among spectators regarding the fairness of the legal system. Throughout the play, the vulnerability of innocent individuals who are left defenseless and the portrayal of justice institutions prioritizing their own interests are highlighted through the elements of epic theatre. The use of elements such as minimal setting, alienation effect, chorus, and music serve as a tool to convey the message to the audience about the theme of justice which is susceptible to manipulation. The objective of this research is to analyze techniques of epic theatre used in the selected work.
Keywords: 5. Gender equality; 16. Peace & justice